Weberian Sociology and Portrait of Contemporary Sufism Studies - Abdul Kadir Riyadi (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2020)
Applying Weberian sociology to the study of Islam is a problematic undertaking. This paper highlights the difficulties in reconciling the Western approach to the study of religion and Islam with the principles of objective and unbiased scholarship. Max Weber is considered one of the fathers of modern sociology, yet his major works largely ignore Islam and Muslim society. If he mentions Islam, then only briefly and with a lot of misgivings. Weber’s persistent bias towards Islam has generated a lot of consternation in Muslim circles and has given rise to much speculation and debate. Some of Weber’s intellectual heirs have tried to fill this gap and included Islam in their research. Although the result is often unbalanced and unsympathetic, his successors have enriched the sociological study of Islam and Sufism. Weber’s modern critics have refuted his major hypotheses and introduced a more objective approach to the study of Islam and Sufism. The ongoing dispute between the Weberians and their opponents on the nature of Sufism invites further discussion. This paper is aimed at examining this debate exploring the richness of spiritual Islam as studied by Weberian sociologists and their critics.